Urban Processes and Social Inequality: From the First Cities to the Possibility of New Egalitarian Communities - Aletta, Luciano (2023)
Urban inequality can be defined as the difference in living conditions between people of the same urban agglomeration. A disparity of status that stands out in the physical structure of the urban fabric – such as in the presence or absence of public transport, basic infrastructure networks, public spaces, schools, healthcare centers or housing provision – but above all in the possibilities of its inhabitants to get access to land and to take part in the democratic process of city-making. But how such an imbalance is produced and what is the role of the built space within this process of differentiation? Is the urban fabric simply being shaped by this condition, or it has a major role in the production and reproduction of social injustice?